2017
DOI: 10.1038/jp.2017.132
|View full text |Cite
|
Sign up to set email alerts
|

Maternal magnesium therapy, neonatal serum magnesium concentration and immediate neonatal outcomes

Abstract: The between-group differences highlight that there is a therapeutic range of neonatal serum magnesium concentrations for neuroprotective effects of antenatal magnesium sulfate, while concentrations outside of this range may be associated with adverse neonatal outcomes. Further studies are needed to determine the optimal dose and duration of maternal magnesium to minimize adverse neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
2
15
0
2
Order By: Relevance
“…), including potential for increased risk of intraventricular haemorrhage and neonatal morbidity (Narasimhulu et al . ). Studies of MgSO 4 given to newborns suggest that bolus doses of between 125 and 250 mg kg −1 given repeatedly every 24 h have little effect on seizures, possibly because of the relatively limited transfer of MgSO 4 from blood to the brain (Ichiba et al .…”
Section: Discussionmentioning
confidence: 97%
“…), including potential for increased risk of intraventricular haemorrhage and neonatal morbidity (Narasimhulu et al . ). Studies of MgSO 4 given to newborns suggest that bolus doses of between 125 and 250 mg kg −1 given repeatedly every 24 h have little effect on seizures, possibly because of the relatively limited transfer of MgSO 4 from blood to the brain (Ichiba et al .…”
Section: Discussionmentioning
confidence: 97%
“…There is still a lack of evidence, and conflicting results about the effect of antenatal MgSO 4 on both cerebral oxygenation and the incidence of severe IVH, and the reports suggest that outcomes may depend on the antenatal maternal magnesium dose/serum concentrations and neonatal serum magnesium concentrations. [21][22][23][24][25][26][27][28] Despite the uncertainty about the exact mechanism of fetal MgSO 4 neuroprotection, some factors have been asserted to have a role in lowering CP risk. MgSO 4 was shown to have multiple direct effects on the nervous tissue, such as blockade of NMDA (N-Methyl-d-aspartate) receptors and increasing angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Provided that neonatal serum magnesium concentrations are <4.5 mEq dl −1 , MgSO 4 has powerful neuroprotective effects (Narasimhulu et al . ). Neonatal (and presumably, fetal) serum concentrations correlate closely with the total maternal dose and duration of therapy, and serum concentrations between 2.5 and 4.5 mEq dl −1 are optimal for neuroprotection, whereas concentrations >4.5 mEq dl −1 may be associated with periventricular leukomalacia (Narasimhulu et al .…”
Section: Introductionmentioning
confidence: 97%
“…Neonatal (and presumably, fetal) serum concentrations correlate closely with the total maternal dose and duration of therapy, and serum concentrations between 2.5 and 4.5 mEq dl −1 are optimal for neuroprotection, whereas concentrations >4.5 mEq dl −1 may be associated with periventricular leukomalacia (Narasimhulu et al . ). Of note, this study also identified increased risk of grade 3–4 intraventricular haemorrhage in neonates with serum concentrations <2.5 mEq dl −1 , suggesting there are some pregnancies that would benefit from maternal magnesium supplementation.…”
Section: Introductionmentioning
confidence: 97%